2006
DOI: 10.1002/cbf.1204
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ω-3 essential fatty acids against formaldehyde-induced neuronal damage in prefrontal cortex of rats

Abstract: The aim of this study was to examine the neurotoxicity of formaldehyde on prefrontal cortex and the protective effects of omega-3 essential fatty acids against these toxic effects. For this purpose, 21 male Wistar rats were divided into three groups. The rats in group I comprised the controls, while the rats in group II were injected every other day with formaldehyde (FA). The rats in group III received omega-3 fatty acids daily while exposed to formaldehyde. At the end of the 14-day experimental period, all r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 41 publications
4
60
0
5
Order By: Relevance
“…FA exhibits antimicrobial activity, and it performs a fixative function in non-viable tissues. [26][27][28] It has been reported that FA has toxic effects on the skin, respiratory system, nervous system, gastrointestinal system and urinary system, as well as allergic effects. In addition, there are available data in the literature regarding the symptoms and side effects of FA on several systems (Table 2).…”
Section: Formaldehyde Usesmentioning
confidence: 99%
“…FA exhibits antimicrobial activity, and it performs a fixative function in non-viable tissues. [26][27][28] It has been reported that FA has toxic effects on the skin, respiratory system, nervous system, gastrointestinal system and urinary system, as well as allergic effects. In addition, there are available data in the literature regarding the symptoms and side effects of FA on several systems (Table 2).…”
Section: Formaldehyde Usesmentioning
confidence: 99%
“…It was also reported that FA is capable of damaging the prefrontal cortex, including the hippocampus of rats [48] [49]. Mohamad et al [67] [75] and changes in gene expression signatures [74].…”
Section: Experimental Studymentioning
confidence: 99%
“…4,5 DHA özellikle beyin, retina ve diğer nöral dokularda yoğun olarak bulunan bir yağ asididir. Kısa zincirli bir ω-3 yağ asidi olan ALA sağlıklı erişkinlerin metabolizmasında yer alır.…”
Section: Gereç Ve Yöntemunclassified
“…4,5,20 Organizmada herhangi bir patolojik olay sonucunda yada fizyolojik koşullarda oluşan serbest radikaller ile bunların koruyucusu olan antioksidan savunma sistemi arasında bir denge söz konusudur. Bu dengenin serbest radikaller lehine kayması oksidatif stresi gösterir.…”
Section: -19unclassified